SPECC1L-deficient primary mouse embryonic palatal mesenchyme cells show speed and directionality defects - Jeremy P. Goering (Nature Portfolio, 2021)
Abstract Cleft lip and/or palate (CL/P) are common anomalies occurring in 1/800 live-births. Pathogenic SPECC1L variants have been identified in patients with CL/P, which signifies a primary role for SPECC1L in craniofacial development. Specc1l mutant mouse embryos exhibit delayed palatal shelf elevation accompanied by epithelial defects. We now posit that the process of palate elevation is itself abnormal in Specc1l mutants, due to defective remodeling of palatal mesenchyme. To characterize the underlying cellular defect, we studied the movement of primary mouse embryonic palatal mesenchyme (MEPM) cells using live-imaging of wound-repair assays. SPECC1L-deficient MEPM cells exhibited delayed wound-repair, however, reduced cell speed only partially accounted for this delay. Interestingly, mutant MEPM cells were also defective in coordinated cell movement. Therefore, we used open-field 2D cultures of wildtype MEPM cells to show that they indeed formed cell streams at high density, which is an important attribute of collective movement. Furthermore, activation of the PI3K-AKT pathway rescued both cell speed and guidance defects in Specc1l mutant MEPM cells. Thus, we show that live-imaging of primary MEPM cells can be used to assess mesenchymal remodeling defects during palatal shelf elevation, and identify a novel role for SPECC1L in collective movement through modulation of PI3K-AKT signaling.